Instruments of foreign trade finance of Dhaka Bank Limited : CPC trade operations - Paul, Reynold Immanuel (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015